ผลกระทบของการวางตำแหน่ง ภาพลักษณ์ คุณค่า และการประชาสัมพันธ์ต่อแนวโน้มการเชียร์สโมสรบาสเกตบอลไฮเทค - ปฏิภาณ กล้าหาญ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The purpose of this study is to examine the brand positioning, brand value, and brand image of the product and the relationship of marketing communication. It aims to study the trend in choosing Hitech Basketball Club as a support team using an online survey as a tool to collect data from a sample group of 400 Hitech Basketball Club fans. The survey was distributed through the Inbox Page of the Hitech Basketball Club fans followed on Facebook. Analyzing the obtained data to find the percentage, standard deviation, and Pearson correlation coefficient from the study of the opinion level of the sample group showed that the overall  opinions on brand positioning of the Hitech club, brand image of the Hitech club, brand value of the Hitech club and trend in selecting Hitech club as a support team are rated highly. In general, opinions on sports promotion are of moderate importance. The hypothesis test results showed that brand positioning of the Hitech club (r = 0.533), brand image of the Hitech club  (r = 0.676), brand value of the Hitech club (r = 0.705), and sports promotion (r = 0.710) have a statistically relationship with the trend in selecting the Hi-Tech team as a support team at the significant level 0.05.